2020
DOI: 10.1002/ieam.4298
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Pesticide Contamination of Wetlands in the Great Barrier Reef Catchment Area

Abstract: Knowledge of the types and impacts of contaminants occurring in the freshwater wetlands of the Great Barrier Reef catchment area (GBRCA) is limited. The present study examined the presence and concentrations of pesticides occurring in 22 floodplain wetlands, situated in moderate to high-intensity land uses in the GBRCA. The dominant land use within 1 km of the wetlands was sugar cane for 12 wetlands, grazing for 6 wetlands, plantation forestry and conservation for 2 wetlands, and one with an equal mix of land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For instance, pesticides can change the reproduction fitness of barramundi [14], and fertilisers can cause weed proliferation [15]. Currently, the assessment and monitoring of pollution in wetlands of the Great Barrier Reef catchments has been conducted through intensive temporal and spatial sampling [16,17] or the evaluation of the use of fertilisers and pesticides [12]. In these and other catchments with intense agricultural land-use, identifying the sources of contaminants at the species level could complement these efforts and be particularly useful to identify sources that are not necessarily close by.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pesticides can change the reproduction fitness of barramundi [14], and fertilisers can cause weed proliferation [15]. Currently, the assessment and monitoring of pollution in wetlands of the Great Barrier Reef catchments has been conducted through intensive temporal and spatial sampling [16,17] or the evaluation of the use of fertilisers and pesticides [12]. In these and other catchments with intense agricultural land-use, identifying the sources of contaminants at the species level could complement these efforts and be particularly useful to identify sources that are not necessarily close by.…”
Section: Introductionmentioning
confidence: 99%
“…Both Warne et al (2020) and Spilsbury et al (2020) reported >80 % of samples from monitored GBR waterways contained PAI mixtures. Similarly, Vandergragt et al (2020) found that all of the 22 monitored wetlands in the GBR catchment area contained between 12 and 30 PAIs at each sampling period. To protect the GBR from the harmful effects of PAIs and other aquatic pollutants (i.e., suspended solids (eroded soil), and nutrients (nitrogen and phosphorus)) the Australian and Queensland governments have developed the Reef 2050 Water Quality Improvement Plan (Reef 2050 WQIP) (Australian Government and Queensland Government, 2018).…”
Section: Introductionmentioning
confidence: 64%
“…Another common source of conflict surrounds the negative effects of chemical run-off on surrounding ecosystems (Packer, 2019). Although the negative effects of chemical run-off on the environment (and on people) is increasingly well known, pesticide and herbicide application (often above recommended limits) is frequently applied to areas close to important natural ecosystems (Edge et al, 2020;Vandergragt, Warne, Borschmann, & Johns, 2020). We highlight this in Table 1 with an example of someone applying herbicide close to a national park.…”
Section: What Role Can Nonviolent Communication Play In Conservation Science?mentioning
confidence: 99%